Swap the variables:
x=3y−3

Solve for y. Add 3 to both sides: x+3=3y−3+3

x+3=3y

Multiply both sides by \(\displaystyle\frac{{1}}{{3}}\): \(\displaystyle\frac{{1}}{{3}}{\left({x}+{3}\right)}=\frac{{1}}{{3}}{\left({3}{y}\right)}\)

PSK1/3x+1=y

or

\(\displaystyle{y}=\frac{{1}}{{3}}{x}+{1}\)

Solve for y. Add 3 to both sides: x+3=3y−3+3

x+3=3y

Multiply both sides by \(\displaystyle\frac{{1}}{{3}}\): \(\displaystyle\frac{{1}}{{3}}{\left({x}+{3}\right)}=\frac{{1}}{{3}}{\left({3}{y}\right)}\)

PSK1/3x+1=y

or

\(\displaystyle{y}=\frac{{1}}{{3}}{x}+{1}\)